Leveraging Technology in English Language Learning - Bianca Maria Talitha Karsudjono (Indonesia Technology-Enhanced Language Learning (iTELL) Journal, 2024)
Technology gets through all aspect of life, and it is inevitable. So, it is mandatory to put technology such as artificial intelligence (AI) in teaching learning activity, especially in high school. In SMA Banua Kalsel where students rarely got their gadgets to study in class, devices such as, laptop and phone is limited. The scope of this study is technology applications (ChatGPT, Quizizz, and Wordwall) in teaching learning activity, students’ engagement, and students’ understanding of learning English with technology. This research is descriptive research with qualitative method. It will gather, structure, and interpreting data on teaching learning English in class with AI technology. Action research is used to conduct the research. The action research format involves initial exploratory analysis and action strategy development. After doing the research there are some ideas which can be concluded. When the learning activity use AI, Students have more active engagement in learning activity and enhance students understanding. Limited time in using devices does not limited students’ ability to operate and use technology applications. Using technology on test gives extra enhancement on students score. Even though most of students enhance their understanding when learning with technology, there are students who doesn’t match with technology.